Newnes electrical power engineer's handbook - Warne, D. F. (Newnes, 2005)
The second edition of this popular engineering reference book, previously titles Newnes Electrical Engineer's Handbook, provides a basic understanding of the underlying theory and operation of the major classes of electrical equipment. With coverage including the key principles of electrical engineering and the design and operation of electrical equipment, the book uses clear descriptions and logical presentation of data to explain electrical power and its applications. Each chapter is written by leading professionals and academics, and many sections conclude with a summary of key standards. Th.